Beyond Proficiency: Assessing Coaching Competence in School Principal Candidates and Uncovering Pathways for Growth - Ratna Juwita; Eka Budhi Santosa; Fatma Sukmawati (IKIP PGRI Bojonegoro, 2024)
As educational leadership increasingly recognizes the pivotal role of coaching competence, this study delves into the nuanced landscape of coaching competencies exhibited by a cohort of 2022 school principal candidates. Amidst the expectations for exemplary instructional leadership, this study reveals a disconcerting reality – school principal candidates exhibit coaching competence only at a fair level, falling short of the desired excellence. Utilizing a descriptive qualitative research design, the authors scrutinized the coaching competence of a diverse cohort of principal candidates through questionnaires and in-depth interviews. Results illuminate specific challenges in coaching, ranging from limited practical application of coaching skills to gaps in mentorship opportunities. Despite the fair level of competence, the study identifies untapped opportunities for improvement, suggesting tailored training and professional development initiatives. The findings not only contribute to the current discourse on coaching competence but also underscore the critical need for targeted interventions to elevate the proficiency of school principal candidates in navigating the complexities of educational leadership.